The Influence of Product, Location and Service Quality On Purchasing Decisions Donuts Baby Sungai Penuh - Fauzan, Muhammad; Saputra, Rizky Indra; Setiono, Agus; Regen (PT Katersi Minar Permata, 2025)
This study aims to determine: 1) Do product, location and service quality have partial and simultaneous influence on the decision to purchase baby donuts? 2). How big is the influence of product, location and service quality partially and simultaneously on the decision to buy baby donuts? The research methodology used is descriptive qualitative and descriptive quantitative approaches. The research results are; 1) Partially there is an effect of product on purchasing decisions, partially there is influence of location on purchasing decisions, partially there is no influence of service quality on purchasing decisions, and simultaneously there is influence of product, location, quality of service on purchasing decisions. 2) partially, the magnitude of the influence of the product on purchasing decisions is 17.18%., the magnitude of the influence of location on purchasing decisions is 12.83%, the magnitude of the influence of service quality on purchasing decisions is 1.71%. And Simultaneously the amount of influence between product, location and quality of service on purchasing decisions is 31.7%.